Aplicative Construction in Lamalera Dialect of Lamaholot Language - Demon, Yosef; Pastika, I Wayan; Artawa, Ketut; Udayana, I Nyoman (e-Journal of Linguistics, 2017)
The applicative construction is limited as (i) the creation of a new argument of inner objects and (ii) the advancement of a peripheral constituent (locative, instrumental, benefactive, and source) occupying the position of the core argument (object). Thus, applicative constructs include the creation of new objects and the advancement of peripheral arguments occupying the core argument.   Each language has a strategy in getting around the applicative construction. Agglutinative languages for example, deal with morphological applicative construction. Unlike Lamalera dialect of Lamaholot language(LDLL) which is not an agglutinative language. Lamalera dialect of Lamaholot language has a morphophonogical strategy such as sound alternation or internal modification and syntactic strategy of word order. Both LDLL applicative construction strategies will be presented in this article.